Use of Objective Structured Clinical Examinations (OSCE) as a Valid and Reliable Assessment Tool in Medical Education - Salam, Abdus; Alsharkawy, Alsayed; Abdelhalim, Abdelbaset Taher; Satwi, Sapari; Mohd Taibi, Muhd Khairi Bin; Hassan, Khaled Mat (International Journal of Human and Health Sciences (IJHHS), 2024)
Abstract not available International Journal of Human and Health Sciences Vol. 08 No. 01 Jan’24 Page: 3-8